2021
DOI: 10.1038/s41598-021-82093-8
|View full text |Cite
|
Sign up to set email alerts
|

Detection of hydroacoustic signals on a fiber-optic submarine cable

Abstract: A ship-based seismic survey was conducted close to a fiber-optic submarine cable, and 50 km-long distributed acoustic sensing (DAS) recordings with air-gun shots were obtained for the first time. We examine the acquired DAS dataset together with the co-located hydrophones to investigate the detection capability of underwater acoustic (hydroacoustic) signals. Here, we show the hydroacoustic signals identified by the DAS measurement characterizing in frequency-time space. The DAS measurement can be sensitive for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 57 publications
2
50
0
Order By: Relevance
“…Observations from other underwater cables (e.g. Matsumoto et al, 2021;Sladen et al, 2019; showed that primary and especially secondary microseismic activity was visible all along the cable. This difference in TF with previous observations is probably due to several factors, among them the low strain coupling between cable and ground.…”
Section: Noise Analysismentioning
confidence: 96%
See 1 more Smart Citation
“…Observations from other underwater cables (e.g. Matsumoto et al, 2021;Sladen et al, 2019; showed that primary and especially secondary microseismic activity was visible all along the cable. This difference in TF with previous observations is probably due to several factors, among them the low strain coupling between cable and ground.…”
Section: Noise Analysismentioning
confidence: 96%
“…Fiber-optic seismology gained popularity in the oil and gas industry a decade ago but its interest is growing rapidly in a variety of geophysical applications. Some of them include: active-source hydroacoustic monitoring in the ocean (Matsumoto et al, 2021), CO 2 storage monitoring (Trautz et al, 2020), imaging of marine sediments (Spika et al, 2020), urban seismology (Lindsey et al, 2020;Zhu et al, 2021), seismic properties of glaciers (Booth et al, 2020), teleseismic studies (Yu et al, 2019), characterization of thunder-induced ground motions (Zhu and Stensrud, 2019), active-source seismic tomography (Parker et al, 2018), and ambient noise interferometry and earthquake seismology (Ajo-Franklin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, works have appeared [ 149 ], where an underwater optical cable is used as a hydroacoustic array. Compared to traditional hydrophones, DAS-based technologies are inferior in sensitivity in the high-frequency region, and in the low-frequency region (below 10 Hz) they compete with piezoelectric sensors [ 149 ]. The advantage may be the simplicity of providing multiple measurement channels.…”
Section: Das In Geophysics (Boris G Gorshkov)mentioning
confidence: 99%
“…Acoustic sensing in optical fibers is emerging as one of the most important technologies in submarine seismic monitoring applications [9][10][11]. The sole reason is the fact that existing submarine infrastructure can be converted into seismic and wave sensors by simply connecting the interrogator unit to many (already deployed) optical fibers in seabed cables.…”
Section: Long Distance Range-submarine Cables Measurementsmentioning
confidence: 99%